2016
DOI: 10.1097/qad.0000000000001045
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of anal cancer screening in HIV-positive and negative MSM

Abstract: The high prevalence of high-risk-HPV and frequency of false negative cytology in this study suggest that high-resolution anoscopy would have most clinical utility, as a primary screening tool for anal cancer in a high-risk group. The prevalence of AIN3+ in HIV-positive MSM lends support for a policy of screening this group, but the high prevalence of lower grade lesions which do not warrant immediate treatment and the limitations of treating high-grade lesions requires careful consideration in terms of a scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 15 publications
5
56
2
Order By: Relevance
“…Our results are consistent with previous studies which also reported high tolerability of HRA among MSM and men with HIV infection . Our study contributes data on the acceptability of HRA among women, and provides more comprehensive measures of lack of tolerability of HRA through evaluation of both objective clinical measures and subjective patient‐reported measures in a greater number of patients.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with previous studies which also reported high tolerability of HRA among MSM and men with HIV infection . Our study contributes data on the acceptability of HRA among women, and provides more comprehensive measures of lack of tolerability of HRA through evaluation of both objective clinical measures and subjective patient‐reported measures in a greater number of patients.…”
Section: Discussionmentioning
confidence: 92%
“…Schofield et al . found that pain was generally ranked low and 92.4% of MSM would attend anal screening in the future. Hillman et al .…”
Section: Discussionmentioning
confidence: 99%
“…58 A third study evaluated the feasibility and acceptability of anal screening among HIV seropositive men. 59 The high prevalence of high-risk HPV serotypes and the frequency of false-negative cytology suggested that HRA would have most clinical benefits as a primary screening strategy for anal cancer in this high-risk group. The analysis was hampered, however, by uncertainty as to how best to monitor those participants with lower grades of AIN.…”
Section: Anal Cancermentioning
confidence: 99%
“…A lack of comprehensive data concerning the natural history of anal cancer and the possibility of preventing this cancer through the identification and treatment of high‐grade anal intraepithelial neoplasia (HGAIN) mostly hampers the development of specific guidelines. Despite these facts, several hospital‐level experiences in anal cancer screening are being increasingly reported . They mostly rely on a digital anorectal examination to detect early‐stage cancer or anal cytology in combination with other diagnostic procedures when abnormal results are found.…”
Section: Introductionmentioning
confidence: 99%